The Effect Of Advertising Creativity On Brand Selection Decisions E-Commerce For Career Women In Indragiri Hulu Regency - Ningsih, Fitria; Afriaris, Said (Journal of Industrial Engineering & Management Research, 2021)
— Media planning is a very important activity in advertising and promotion. A well-prepared media plan will result in effective communication so that the message conveyed will receive greater attention from the target audience. In this case, the type of product (goods and services) advertised affects the choice of media. Certain types of products are sometimes more suitable to be advertised through television media but other products are more suitable if using print media or other media. The aims of the research are: To determine the effect of Attention, Interest, Desire, and Action in the consideration of career women partially on the decision to choose an E-Commerce Brand. To determine the effect of Attention, Interest, Desire, and Action in the consideration of career women partially on the decision to choose an E-Commerce Brand. And to determine the influence of Attention, Interest, Desire, and Action which factors have a dominant influence on the consideration of career women in the decision to choose an E-Commerce Brand. In its implementation, explanatory researchers use survey research methods, where information is collected from respondents using questionnaires. survey research is research that takes a sample from one population and uses a questionnaire as the main data collection tool. This approach uses a quantitative approach is research that in the process of implementation uses a rigorous research design in the form of numbers or with statistical formulas or other methods of quantification to measure the research variables. Based on the analysis and discussion that has been put forward, the conclusions are as follows: From the results of the t test test, it shows that Attention (X1) is 3.123, Interest (X2) is 5.859, Desire (desire) (X3) is 4.792, Action (action) (X4) of 2.870, separately has a significant effect on purchasing decisions (Y) on E-COMMERCE products. From the test results of the f test, it shows that Attention (attention) (X1), Interest (X2), Desire (desire) (X3), Action (action) (X4) together have a significant effect on purchasing decisions (Y) on E-COMMERCE products, namely F-count (28.273) > F-table (2.47). And from all variables Attention (attention) (X1), Interest (interest) (X2), Desire (desire) (X3), Action (action) (X4) obtained after testing the t test, it turns out that the variable Interest (interest) (X2 ) of 5.859 and t-table of 1.985 which has the most dominant influence on purchasing decisions (Y) on E-COMMERCE products.